HADIS TENTANG HAK NAFKAH BAGI WANITA YANG DITALAK TIGA (Kasus Fatimah binti Qais) - LA ODE ISMAIL AHMAD (LPPM IAIN Parepare, 2014)
This paper discusses the rights of living for women divorced by her husband such a case of Fatimah binti Qays, a companion of prophet who divorced by her husband and was not in place. The hadith stated the attitude of Abu Omar divorced his wife while he wasn’t there and sending a representative to meet Fatima bint Qais and bring her some foods. A representative’s visiting made Fatimah felt unsatisfactory because the food (nafkah) brought was not enough to supply her daily needs. This Hadith related to the issue both its sanad and matan are shahih (authentic quality). Although there is a valid hadith shows that there is no right of living for a husband to his divorced wife, but some scholars still disagree about it because of the texts of the Qur'an manage about the rights of living and housing.